Profit Shifting opportunities, Multinationals, and the determinants of FDI - Sven Stöwhase (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2002)
The theory of tax competition suggests that different tools might be used to attract physical capital and taxable profits. While it is assumed that FDI in real activity is deterred by high effective taxes, investment undertaken for purpose of profit-shifting is deterred by a higher statutory tax rate. Using information from the RWI-Database "Globalisation", which contains statistics about foreign engagements of the most important German enterprises, this paper investigates if this assumption holds in reality. Differentiating between the functional form of engagement and using a linear regression, the analysis provides evidence that FDI in real activity (production) is correlated with effective tax rates while FDI that implies more opportunities for profit shifting activities (service, finance and R&D) is correlated with the tatutory tax rate.
urn:nbn:de:bvb:19-epub-29-1
Keywords: F23; H25; H26; H32; 330; foreign direct investment; profit shifting; multinational corporations